Health education with your family and ostomized patients: chance for better quality of life - Camila Fernandes Wild; Natalia Barrionuevo Favero; Cléton Salbego; Michele Gonçalves de Vale; Jonatan da Rosa Pereira da Silva; Tierle Kosloski Ramos (Universidade Federal de Santa Maria, 2016)
Aim: to report the nurses' experience with the realization of educational activities with ostomized patients and their families in a Family Health Strategy from the West Frontier of the Rio Grande do Sul. Method: experience report on the conduction of educational activities with a group of ostomized patients and their families, developed during the period of six months by the professional staff of the Family Health Strategy. The educational proposal happened under a perspective of conversation circles, which led to the sharing of scientific and popular knowledge among the participants. The aim was to encourage self-care and family participation in the process. Results: in the education group issues related to food, sexuality, self-care and self-image were discussed, besides basic care with the stoma and management of the stoma bag. Final Remarks: the proposal has contributed to the improvement of patients' quality of life by clarifying relevant questions that arise naturally by their condition